RELAÇÕES INTERORGANIZACIONAIS COMO LÓCUS DE VANTAGEM COMPETITIVA: MANIFESTAÇÕES EM INSTITUIÇÕES BRASILEIRAS DE EDUCAÇÃO SUPERIOR - Fábio Dal-Soto (Universidade Federal de Santa Catarina, 2017)
Interorganizational relationships have been established as important locus of generating competitive advantages and consequently an interesting analysis unit for understanding the competitive advantage . From this, the aim of this paper is to analyze the development of these relations as sources of competitive advantages, through the Consortium of Community Universities Gaucho (COMUNG), composed of 15 community institutions of higher education, located in southern Brazil. Thus, it’s a single case study with multiple units of analysis, accomplished through in loco interviews with the President of the Consortium and the managers of the researched institutions, as well as secondary data. The results show a set of actions accomplished by COMUNG as sources of relational advantages, such as joint political movement, sharing administrative and academic experiences and the establishment of tacit agreements of competition. Therefore, the insider position in COMUNG gives opportunity to institut ions learning faster, reducing costs and sharing, the safeguarding geographical areas of competition and the qualification and differentiation of activities in general.